Deciphering the footprints of predator–prey interactions on coral reefs: seasonal dynamics and environmental drivers of reef halos - Emily K. Lester; Michael V.W. Cuttler; Tim J. Langlois; Elizabeth M.P. Madin (Coral Reefs, 2025)
Landscape-scale footprints of behavioural interactions between predators and prey can offer a window into the ecological dynamics of entire ecosystems. In coral reefs, a promising example of this phenomenon includes reef halos, which are bare patches of sand surrounding patch reefs. Reef halos form where the presence of predators restricts herbivory and other foraging activities to close proximity of shelter. Additionally, reef halos persist from year-to-year, are more prevalent in reefs with ostensibly intact predator populations, and are easily measured using satellite imagery. However, the stability of reef halos over short-term (i.e. monthly) scales and how they respond to environmental factors, has yet to be rigorously explored in coral reefs. Here, we used a remote sensing approach to investigate the magnitude of reef halo size fluctuations over time in the Ningaloo Reef, Western Australia, relative to a suite of environmental factors. Although reef halos appear to be a permanent feature of the seascape, the size of individual reef halos fluctuated widely over monthly scales, declining as sea surface temperature and regional upwelling (a proxy for nutrient delivery) increased. We did not find a relationship between halo prevalence and management zone, fish biomass, or patch reef area, which is inconsistent with studies of reef halo formation in other locations. Unravelling this discrepancy with the broader literature will require an in situ experimental approach. Overall, our results demonstrate that single snapshots in time of reef halo size may not be sufficient to yield accurate signals regarding interactions between predators, herbivores, and vegetation.